2011
DOI: 10.1021/ac2014349
|View full text |Cite
|
Sign up to set email alerts
|

Direct Demonstration of Tissue Uptake of an Inhaled Drug: Proof-of-Principle Study Using Matrix-Assisted Laser Desorption Ionization Mass Spectrometry Imaging

Abstract: Drug therapy is often directed to specific organ and tissue compartments where the mode of action of the compound affects specifically targeted biological processes. However, the direct measurement of drug uptake in terms of a time kinetic and concentrations attained at the local sites has not been readily available as a clinical index for most drugs. A proof-of-principle study was conducted to test the utility of applying matrix-assisted laser desorption ionization-mass spectrometry imaging (MALDI-MSI) to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…However, although cumbersome, temporal information from in vivo experiments can be collected and, by this, drug-tissue interactions be described in more detail [12]. Several successful attempts have been made in the lung, where the tissue localization of an inhaled anticholinergic was determined in a rodent inhalation model [13,14], as well as in a clinical study in COPD patients inhaling therapeutic doses [12,15]. The above mentioned in situ techniques are explained in an excellent review paper by Solon et al [16].…”
Section: Tissue Dispositionmentioning
confidence: 99%
“…However, although cumbersome, temporal information from in vivo experiments can be collected and, by this, drug-tissue interactions be described in more detail [12]. Several successful attempts have been made in the lung, where the tissue localization of an inhaled anticholinergic was determined in a rodent inhalation model [13,14], as well as in a clinical study in COPD patients inhaling therapeutic doses [12,15]. The above mentioned in situ techniques are explained in an excellent review paper by Solon et al [16].…”
Section: Tissue Dispositionmentioning
confidence: 99%
“…The distribution of the multiple-receptor tyrosine kinase inhibitor AEE788 in rodent prostate cancer models was analyzed by MALDI-MSI (35). The tyrosine kinase inhibitors erlotinib and gefitinib have been analyzed, after depositing single droplets of drugs on tissue slices of planocellular lung carcinoma, adeno-carcinoma and large cell lung carcinoma (36)(37)(38). Yasunaga et al (39) showed that paclitaxel-incorporating micelles deliver more paclitaxel to the tumor and less paclitaxel to normal tissue, as compared with treatment with paclitaxel alone.…”
Section: Mass Spectrometry Imaging (Msi) Mass Spectrometry Imaging (Msi)mentioning
confidence: 99%
“…Consequently, quantitative MSI was rapidly applied to evaluate the distribution of drug compounds (Solon et al 2010;Nilsson et al 2010;Koeniger et al 2011;Takai et al 2012;Lietz et al 2013). Recently, high resolution MSI provided a significant advantage of autoradiography from the aspect of the drug metabolites (Fehniger et al 2011;Jirasko et al 2014;Liu et al 2013;Buck et al 2015) and demonstrated the distribution of a confirmed drug metabolite that possibly lead to the drug toxicity (Török et al 2015). The technology is today making important contributions in fields such as PK screening (Castellino et al 2013), novel pro-drug concepts (Nilsson et al 2010;Fehniger et al 2011), drug delivery systems (DDS) by micellar nanoparticle formulation (Swales et al 2014), biomarkers for PD (Yasunaga et al 2013;Shariatgorji et al 2014;Cobice et al 2013) as well as proteomics (Goto et al 2014;Ye et al 2014).…”
Section: Drug Metabolism and Pharmacokinetics (Dmpk)mentioning
confidence: 99%
“…Patients in feasibility studies in combination with disease models in rodents has been the strategy of our research teams for a number of years (Fehniger et al 2011;Marko-Varga et al 2012;Sugihara et al 2014;Török et al 2015). Further, the correlation in-between a given rodent model with administered drug and the ability to utilize controlled administrations to tissue sections from organs isolated with the intact tumor environment is a valuable tool for drug characterizations.…”
Section: Drug Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation